Simultaneous Quantification of Anti-retroviral Drugs Atazanavir, Lamivudine, Tenofovir, and Ritonavir in Bulk and Pharmaceutical Formulation by RP-HPLC - Garlapati, Achaiah (Asian Journal of Pharmaceutics (AJP), 2024)
Objective: Quality is important in every product or service, but it is vital in medicine as it involves life. Therefore, analytical methods which are a measure of quality of the drugs play a very comprehensive role in drug development and follow-up activities. As like any drug, the perfect estimation of the quality and quantity of the anti-viral drugs with respect to their potency, safety, and dosage etc., is the need of the hour so that these drugs will serve the actual purpose for which they are intended. Materials and Methods: The chromatographic separation was achieved using Waters C8 (100 × 4.6 mm ID) 1.7 μm column, and isocratic mobile phase consists potassium phosphate buffer pH3.5:acetonitrile (55:45) %v/v with a flow rate of 1.0 mL/min. The detection was carried out at 280 nm. The current method was validated according to the ICH guidelines for accuracy, precision, linearity, specificity, robustness, and ruggedness. Results: The retention times obtained for atazanavir (ATZ), lamivudine (3tc), tenofovir, and ritonavir (RTV) were 2.05, 3.33, 4.56, and 6.97 min, respectively. The calibration curves of peak area versus concentration were linear from 15 to 45 μg/mL for Atazanavir (ATV), 3TC, tenofovir disoproxil fumarate, and 5–15 μg/mL and had regression coefficient (r2) 0.999. Limit of detection was found to be 1.2, 0.9, 0.5, 0.2 μg/mL and limit of quantification was found to be 3.6, 2.8, 1.8, 0.8 μg/mL, respectively, for ATZ, 3TC, tenofovir, and RTV. The % assay of the marketed dosage form was found to be 99.8, 99.5, 100.2, and 99.4 for ATZ, 3TC, tenofovir, and RTV. Conclusion: The experimental study results revealed the suitability of proposed method that can be used for simultaneous estimation of ATZ, 3TC, tenofovir, and RTV in bulk and their pharmaceutical formulations for routine quality control analysis.